Testing the Easterlin hypothesis with panel data: The dynamic relationship between life satisfaction and economic growth in Germany and in the UK - Tobias Pfaff; Johannes Hirata (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2013)
Recent studies focused on testing the Easterlin hypothesis (happiness and national income correlate in the cross-section but not over time) on a global level. We make a case for testing the Easterlin hypothesis at the country level where individual panel data allow exploiting important methodological advantages. Novelties of our test of the Easterlin hypothesis are a) long-term panel data and estimation with individual fixed effects, b) regional GDP per capita with a higher variation than national figures, c) accounting for potentially biased clustered standard errors when the number of clusters is small. Using long-term panel data for Germany and the United Kingdom, we do not find robust evidence for a relationship between GDP per capita and life satisfaction in either country (controlling for a variety of variables). Together with the evidence from previous research, we now count three countries for which Easterlin's happiness-income hypothesis cannot be rejected: the United States, Germany, and the United Kingdom. – – Die neuere Forschung hat sich darauf konzentriert die Easterlin-Hypothese (Wohlbefinden und Volkseinkommen korrelieren im Querschnitt, aber nicht in der Zeitreihe) auf globaler Ebene zu testen. Unser Artikel liefert Argumente für das Testen der Easterlin-Hypothese auf nationaler Ebene, wo individuelle Paneldaten das Ausschöpfen wichtiger methodologischer Vorteile ermöglichen. Wir erweitern die bisherige Literatur zur Easterlin-Hypothese durch a) Schätzungen mit individuellen fixen Effekten anhand von längerfristigen Paneldaten, b) Verwendung von regionalem BIP pro Kopf mit einer höheren Varianz als nationale BIP-Daten und c) Berücksichtigung von potentiell verzerrten Cluster-Standardfehlern im Fall von wenigen Clustern. Wir verwenden längerfristige Paneldaten für Deutschland und Großbritannien und finden keine robuste Evidenz für einen Zusammenhang zwischen BIP pro Kopf und Lebenszufriedenheit in den beiden Ländern (unter Verwendung von einer Reihe von Kontrollvariablen). Zusammen mit früheren Forschungsergebnissen zählen wir drei Länder in denen die Easterlin-Hypothese nicht verworfen werden kann: die Vereinigten Staaten, Deutschland und Großbritannien.
Keywords: 330; subjective well-being; economic growth; income; Easterlin hypothesis; Subjektives Wohlbefinden; Wirtschaftswachstum; Einkommen; Easterlin-Hypothese